Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which of the given expressions are equivalent to \( x^{8/5} \), we need to express each of the choices in a similar form and compare them to \( x^{8/5} \).
Let's analyze each option step by step:
#### A. \( \left(x^3\right)^{2 / 5} \)
Applying the rule of exponents \( (a^m)^n = a^{m \cdot n} \):
[tex]\[ \left(x^3\right)^{2 / 5} = x^{3 \cdot \frac{2}{5}} = x^{\frac{6}{5}} \][/tex]
Since \( x^{\frac{6}{5}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### B. \( \sqrt[8]{x^5} \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[8]{x^5} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### C. \( (\sqrt[5]{x})^8 \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[5]{x} = x^{\frac{1}{5}} \][/tex]
Thus,
[tex]\[ (\sqrt[5]{x})^8 = \left(x^{\frac{1}{5}}\right)^8 = x^{\frac{1}{5} \cdot 8} = x^{\frac{8}{5}} \][/tex]
Since \( x^{\frac{8}{5}} = x^{\frac{8}{5}} \), this expression is equivalent to \( x^{8 / 5} \).
#### D. \( \left(x^5\right)^{1 / 8} \)
Applying the rule of exponents \( (a^m)^n = a^{m \cdot n} \):
[tex]\[ \left(x^5\right)^{1 / 8} = x^{5 \cdot \frac{1}{8}} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### E. \( (\sqrt[8]{x})^5 \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[8]{x} = x^{\frac{1}{8}} \][/tex]
Thus,
[tex]\[ (\sqrt[8]{x})^5 = \left(x^{\frac{1}{8}}\right)^5 = x^{\frac{1}{8} \cdot 5} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### F. \( \sqrt[5]{x^8} \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a^m} = (a^m)^{1/n} = a^{m/n} \):
[tex]\[ \sqrt[5]{x^8} = x^{\frac{8}{5}} \][/tex]
Since \( x^{\frac{8}{5}} = x^{\frac{8}{5}} \), this expression is equivalent to \( x^{8 / 5} \).
### Conclusion:
The expressions that are equivalent to \( x^{8 / 5} \) are:
- C. \( (\sqrt[5]{x})^8 \)
- F. \( \sqrt[5]{x^8} \)
Thus, the correct choices are:
[tex]\[ \text{C and F} \][/tex]
Let's analyze each option step by step:
#### A. \( \left(x^3\right)^{2 / 5} \)
Applying the rule of exponents \( (a^m)^n = a^{m \cdot n} \):
[tex]\[ \left(x^3\right)^{2 / 5} = x^{3 \cdot \frac{2}{5}} = x^{\frac{6}{5}} \][/tex]
Since \( x^{\frac{6}{5}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### B. \( \sqrt[8]{x^5} \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[8]{x^5} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### C. \( (\sqrt[5]{x})^8 \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[5]{x} = x^{\frac{1}{5}} \][/tex]
Thus,
[tex]\[ (\sqrt[5]{x})^8 = \left(x^{\frac{1}{5}}\right)^8 = x^{\frac{1}{5} \cdot 8} = x^{\frac{8}{5}} \][/tex]
Since \( x^{\frac{8}{5}} = x^{\frac{8}{5}} \), this expression is equivalent to \( x^{8 / 5} \).
#### D. \( \left(x^5\right)^{1 / 8} \)
Applying the rule of exponents \( (a^m)^n = a^{m \cdot n} \):
[tex]\[ \left(x^5\right)^{1 / 8} = x^{5 \cdot \frac{1}{8}} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### E. \( (\sqrt[8]{x})^5 \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a} = a^{1/n} \):
[tex]\[ \sqrt[8]{x} = x^{\frac{1}{8}} \][/tex]
Thus,
[tex]\[ (\sqrt[8]{x})^5 = \left(x^{\frac{1}{8}}\right)^5 = x^{\frac{1}{8} \cdot 5} = x^{\frac{5}{8}} \][/tex]
Since \( x^{\frac{5}{8}} \neq x^{\frac{8}{5}} \), this expression is not equivalent to \( x^{8 / 5} \).
#### F. \( \sqrt[5]{x^8} \)
Rewriting the radical expression as an exponent, \( \sqrt[n]{a^m} = (a^m)^{1/n} = a^{m/n} \):
[tex]\[ \sqrt[5]{x^8} = x^{\frac{8}{5}} \][/tex]
Since \( x^{\frac{8}{5}} = x^{\frac{8}{5}} \), this expression is equivalent to \( x^{8 / 5} \).
### Conclusion:
The expressions that are equivalent to \( x^{8 / 5} \) are:
- C. \( (\sqrt[5]{x})^8 \)
- F. \( \sqrt[5]{x^8} \)
Thus, the correct choices are:
[tex]\[ \text{C and F} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.